STRUCTURE AND CONTENT OF FOLK CALENDAR OF THE URAL GERMANS - Vayman, D.I. (Perm Federal Research Centre Journal, 2015)
The article, based on the field ethnographic research, held among German inhabitants of the Perm Krai, the Republic of Bashkortostan and Orenburg and Chelyabinsk Oblast, is devoted to the structural peculiarities of the calendar of the Ural Germans inhabitants (cycle of seasonal- phenological changings and traditions of hagiolatry.Calendar fests and rites have been researched in comparison with the published materials of otherRussian German groups and Germans of metropolis which allowed to specify regional, confessional and local aspects of traditions.